Enhancing Drug Utilization Efficiency via Dish-Structured Triboelectric Nanogenerator - Chen, Qu; Deng, Wenjing; He, Jingjin; Cheng, Li; Ren, Pei-Gen; Xu, Yang (Frontiers in Bioengineering and Biotechnology, 2022)
Due to the finding of severe side effects and low therapeutic efficacy with cancer chemotherapy, there still remains a great challenge to benefit patients with curative effect. In this work, we designed a self-powered drug delivery system comprising a current source derived from the disk TENG (D-TENG) and a pair of Au electrodes. Thus, cells seeded within the electrode gap could be stimulated by the current followed by D-TENG`s work. Under the rotation frequency of about 7.4 Hz, the peak output current and voltage of the D-TENG reached 3.7 μA and 135 V and achieved an average of 2.8 μA of output current. Furthermore, the D-TENG also showed its good stability to output steady current in a long-term condition. When applying the electric stimulation by this self-powered drug delivery system, a chemotherapy drug, doxorubicin (DOX), had significant uptake by cancer cells. Therefore, utilizing a novel TENG device as a part of chemotherapy would provide a new opportunity in future disease treatment.